(untitled) (Boletin Médico de Postgrado, 2020)
The goal of this study was to describe the utility of the Khorana model as a risk stratifier for venous thromboembolic disease (VTE) in oncological patients hospitalized in the Servicio de Medicina of the Hospital Central Universitario Dr. Antonio María Pineda during the period February-April 2018. 20 patients were evaluated. The results showed predominance of female sex (1:0.3) with an average age of 52.9 ± 13.1 years. Regarding the location of cancer, the highest percentage (30%) was gynecological followed by digestive (25%) and hematological (15%). According to the histological type of tumor, the highest percentage was carcinoma (82.3%). The distribution of patients according to the type of VTE was deep vein thrombosis in the left lower limb in 65% of cases and pulmonary thromboembolism in 20% of cases. According to the Khorana model, 55% of patients were stratified in the intermediate risk group and 45% in the high-risk group. The use of the Khorana model allowed stratification of most patients at intermediate risk and all within intermediate/high risk. The use of the Khorana model constitutes a useful and applicable tool in the risk stratification of VTE.